Effect of CCNA2 on Prognosis of Colon Cancer by Regulating Immune Microenvironment of Tumor Cells - Peng YANG; Ziyi QIU; Lingling WANG; Yuan HU; Zhengzhen CHEN; Meizhen ZHONG; Feiyue YU; Rongyuan QIU (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the relationship between cyclin A2 (CCNA2) and the prognosis of colon cancer, and its possible mechanism from the perspective of immune infiltration. MethodsWe downloaded the transcriptome data of colon cancer patients from The Cancer Genome Atlas database. Clinicopathological feature analysis and survival analysis were performed based on the expression levels of CCNA2. A total of 75 specimens of colon cancer and normal tissues were collected, and the expression level of CCNA2 was analyzed using immunohistochemical methods. Multivariate analysis was conducted to explore its relationship with clinicopathological features. Gene Set Enrichment Analysis (GSEA) was used to assess the potential molecular functions of CCNA2 in colon cancer. CIBERSORT algorithm was applied to calculate the correlation between CCNA2 and immune-cell infiltration in colon cancer. ResultsDatabase and immunohistochemical analyses indicated that CCNA2 was expressed at a significantly higher level in colon cancer tissues than normal tissues (P<0.001). The overall survival, disease-specific survival, and progression-free interval were all longer in the group with high CCNA2 expression than the group with low expression (all P<0.05). In tumor tissues, the expression level of CCNA2 decreased with increased pathological and TNM stages (P<0.05). The expression level of CCNA2 in normal tissues was consistently lower than that in colon cancer tissues across all clinical stages (all P<0.001). GSEA suggested that Wnt/β-catenin, KRAS, and other signaling pathways were enriched when CCNA2 was lowly expressed. CIBERSORT analysis revealed an increase in the infiltration of immune cells such as regulatory T cells and macrophages M0 when CCNA2 expression was low. ConclusionCCNA2 is highly expressed in colon cancer and closely associated with grade of pathology and TNM stage. It may recruit regulatory T cells through the KRAS and Wnt/β-catenin pathways, thereby reducing immune-cell infiltration and promoting colon cancer progression, leading to poor prognosis.